2013
DOI: 10.1017/s1431927613003036
|View full text |Cite
|
Sign up to set email alerts
|

First Nucleotide Sequence Data from an Electron Microscopy Based DNA Sequencer

Abstract: Extended abstract of a paper presented at Microscopy and Microanalysis 2013 in Indianapolis, Indiana, USA, August 4 – August 8, 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Transmission Electron Microscopy (TEM) has been explored for imaging long DNA segments [ 1 , 2 ] by utilizing high electron energies (80–300 keV) to achieve sub-nanometer resolution. The high impact energy, however, not only produces radiation damage, it necessitates the use of heavy atom labels to provide contrast in the image of the nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission Electron Microscopy (TEM) has been explored for imaging long DNA segments [ 1 , 2 ] by utilizing high electron energies (80–300 keV) to achieve sub-nanometer resolution. The high impact energy, however, not only produces radiation damage, it necessitates the use of heavy atom labels to provide contrast in the image of the nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…For applications where single-strandedness is crucial, as in EM-based DNA sequencing, the strands must be very long and extraction lengths scaled commensurately to ensure that the desired quantity of single-strand segments are deposited. At higher EM resolution, quantification of single-strandedness, base-to-base stretching, and observation of individual nucleotide labeling is possible, though this is beyond the scope of this paper and is discussed elsewhere [24], [25]. However, several qualitative features of threading that can be discerned from high-resolution images are examined in Figure S6 .…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced with permission. [ 161 ] Copyright 2013, Oxford University Press. C) The principle behind heavy atom‐based labeling of DNA and read‐out thereof.…”
Section: Dna Metallization Via Metal Np Staining and Nanowire Growthmentioning
confidence: 99%
“…[ 160 ] While individual bases have been modified in the above studies as a proof‐of‐concept, multiplexing with different contrast‐agent labels in combination with a high‐resolution automated imager allows for direct DNA sequencing from EM‐based images, as demonstrated by Own et al, shown in Figure 12C. [ 161 ]…”
Section: Dna Metallization Via Metal Np Staining and Nanowire Growthmentioning
confidence: 99%